(untitled) (Journal of the College of Basic Education, 2024)
This research presents the roots of comparative semantics in the Arab linguistic heritage, which is considered a modern science that searches for words and their meanings in the languages of one group. The meanings of words in the language are used as a part of the identity of the oldest meaning of the Semitic word. This science appeared after the emergence of comparative application in Sanskrit studies, until the exception of this science among the ancient Arabs, the study focuses on certain references that the ancients intended to root the words and explain their lexical significance. The study found synonymous words and verbal cognates between Arabic and the chosen languages, and the foreign and familiar words in Arabic, have contributed to the research in clarifying the nature of the search for what was mentioned in the writings of the ancient Arabs.